Simulation for decision making: the need for multi-paradigm approaches - Pereira, José Luís (2016)
We are surrounded by complexity and uncertainty that constrain our ability to learn and understand the systems around us. We need tools that allow us to deal more effectively with complexity in order to be able to make better decisions. Simulation is such a tool. It provides the means to experiment and learn from observed behaviour. Simulation can be used to effectively support the evaluation of complex scenarios, however its effectiveness is deeply rooted in the ability to build models that capture all the relevant details and dynamics of a complex system. Several approaches to simulation exist, however we believe that adopting a single simulation approach may prove limiting. In this paper we argue that, in more complex situations, a multi-paradigm simulation approach, in which more than one simulation paradigm is used to study the same reality, may be a better approach.